An Analysis of The Role and Support on Stakeholders of Village Level in The Implementation of Maternal and Child Health Programs Through Optimizing The Utilization of Village Funds in Tegal Regency - Sutopo Patria Jati; Ayun Sriatmi; Martini Martini (Universitas Aisyah Pringsewu, 2021)
Maternal and infant mortality rates are one of the health problems in Indonesia, including at the village level. Currently, the Village has its own authority to manage village funds in an effort to prosper the community. The purpose of the study is analysis the role and support stakeholders in the Maternal and Child Health (MCH) Program through optimizing village funds, with a quantitative design and analytical descriptive approach. The study analyzes the role of stakeholders (attitudes, influencing power, and interests), with respondents, namely village level stakeholders in Tegal Regency who were selected by purposive sampling technique and analysis by Rank Spearman Test. Education has a significant relationship with power of influencing stakeholders (p value= 0.002; CC = 0.561) Stakeholder attitudes and perceptions (p-value = 0.047, CC = 0.379) and power of influence (p-value = 0.017, CC = 0.449) has strong correlation towards optimizing village funds for MCH program. Stakeholder interests (p value=0.003, CC=0.534) have a strong correlation with the implementation of the MCH program in the village. In optimizing allocation village funds, support and the role of stakeholders are needed, especially the attitude and power in making decisions, planning strengths and formulating allocation policies. Likewise, the role of stakeholders in the interests of the MCH program for community welfare will increase multi-sectoral cooperation.Abstrak: Angka Kematian Ibu dan Bayi menjadi salah satu permasalahan kesehatan di Indonesia termasuk di tingkat Desa. Saat ini Desa memiliki wewenang sendiri untuk mengelola dana desa sebagai upaya mensejahterakan masyarakatnya. Tujuan penelitian ini adalah analisis peran dan dukungan stakeholder dalam Program KIA melalui optimalisasi dana desa, dengan desain kuantitatif dan pendekatan deskriptif analitik. Penelitian menganalisis peran stakeholder (sikap, kekuatan memepengaruhi, dan kepentingan), dengan responden yaitu stakeholder tingkat Desa di Kabupaten Tegal yang dipilih berdasarkan teknik purposiv sampling dan dianalisis dengan uji Rank Spearman. Pendidikan memiliki hubungan yang signifikan dengan kekuatan mempengaruhi stakeholder (p value=0.002, CC=0,561) Sikap dan persepsi stakeholder (p value=0.047, CC=0.379) dan kekuatan mempengaruhi (p value=0.017, CC=0.449) memiliki korelasi yang kuat terhadap optimalisasi dana desa untuk program KIA. Kepentingan stakeholder (p value=0.003, CC=0.534) memiliki korelasi yang kuat terhadap pelaksanaan program KIA di Desa. Dalam optimalisasi alokasi dana desa sangat dibutuhkan dukungan dan peran stakeholder terutama sikap dan kekuatan dalam membuat keputusan, merencanakan kekuatan dan merumuskan kebijakan pengalokasian Begitupun dengan peran stakeholder terhadap kepentingan program KIA bagi kesejahteraan masyarakat akan meningkatkan kerjasama multisektor.